2022
DOI: 10.1111/ceo.14035
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of glaucoma: Disease associations, personalised risk assessment and therapeutic opportunities‐A review

Abstract: Glaucoma refers to a heterogenous group of disorders characterised by progressive loss of retinal ganglion cells and associated visual field loss. Both early-onset and adult-onset forms of the disease have a strong genetic component. Here, we summarise the known genetic associations for various forms of glaucoma and the possible functional roles for these genes in disease pathogenesis. We also discuss efforts to translate genetic knowledge into clinical practice, including gene-based tests for disease diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 130 publications
(129 reference statements)
0
16
0
1
Order By: Relevance
“…About 52 XFS including those with glaucoma were screened for the variations and found that allele G of rs3825942 was significantly associated (p = 0.0001) and genotype GG (p = 0.000305) with XFS in our population, which was the first Asian study [83]. Pseudo-exfoliation glaucoma is caused by polymorphisms in the lysyl oxidase like 1 (LOXL1) gene in chromosome 15 with significant associations through GWAS in many populations across the world [81]. Pseudo-exfoliation syndrome, due to the deposition of extracellular fibrillar material (basement membrane, clusterin, elastic fibre contents, elastin, fibrillin-1, laminin, fibronectin, latent TGF-B proteins) crosslinking with LOXL1, hence systemically, it may be associated with cardiovascular diseases, cerebrovascular disorders, dementia like Alzheimer's, pelvic organ prolapse and sensory neural deafness [84].…”
Section: Complex Genetics and Genomics Of Glaucomamentioning
confidence: 95%
See 1 more Smart Citation
“…About 52 XFS including those with glaucoma were screened for the variations and found that allele G of rs3825942 was significantly associated (p = 0.0001) and genotype GG (p = 0.000305) with XFS in our population, which was the first Asian study [83]. Pseudo-exfoliation glaucoma is caused by polymorphisms in the lysyl oxidase like 1 (LOXL1) gene in chromosome 15 with significant associations through GWAS in many populations across the world [81]. Pseudo-exfoliation syndrome, due to the deposition of extracellular fibrillar material (basement membrane, clusterin, elastic fibre contents, elastin, fibrillin-1, laminin, fibronectin, latent TGF-B proteins) crosslinking with LOXL1, hence systemically, it may be associated with cardiovascular diseases, cerebrovascular disorders, dementia like Alzheimer's, pelvic organ prolapse and sensory neural deafness [84].…”
Section: Complex Genetics and Genomics Of Glaucomamentioning
confidence: 95%
“…PCMTD1 (Protein-L-Isoaspartate (D-Aspartate) O-Methyltransferase Domain Containing 1) protein is of the methyltransferase superfamily and ST18 (ST18 C2H2C-Type Zinc Finger Transcription Factor) protein inhibits basal transcription activity through target promoters. There are a myriad of players implicated in PACG as predisposing traits, (extensively reviewed by Ahram et al, Aboobakar and Wiggs) like MTHFR, MFRP, CHX10, HGF, RS; PO1, C3orf26, LAMA2, GJD2, ZNRF3, CD55, MIP, ALPPL2, ZC3H11B, PRSS56, ABCC5, MYOC, CYP1B1, eNOS, PCMTD1, ST18, HSP70, SPARC, CALCRL, EPDR1, CHAT, FERMT2, DPM2, FAM102A and NEB [77,81]. A variety of anatomical, physiological, genetic and environmental factors individually or collectively result in PACG and hence, these associations reveal the larger etiopathogenesis network.…”
Section: Complex Genetics and Genomics Of Glaucomamentioning
confidence: 99%
“…It is well known that glaucoma is markedly affected by genetic factors and is a complex genetic disease ( Aboobakar and Wiggs, 2022 ). There has been evidence suggesting that small variations, including single nucleotide polymorphisms (SNPs) may be underlying cause of glaucoma.…”
Section: Pathogenesis Of Glaucomamentioning
confidence: 99%
“…Besides, these SNPs may play highly pathogenic, mildly pathogenic or protective role in causing glaucoma. Genome-wide association studies (GWAS) is a genome-wide method that compares the genetic profile of SNPs between glaucoma cases and normal groups, aimed at identifying glaucoma-associated genomic regions ( Aboobakar and Wiggs, 2022 ). Thus far, findings of GWAS have implicated 127 genetic loci that show strong associations with primary open-angle glaucoma ( Gharahkhani et al, 2021 ).…”
Section: Pathogenesis Of Glaucomamentioning
confidence: 99%
“… 2 , 3 Despite extensive investigation, intraocular pressure (IOP) is currently the only modifiable risk factor to prevent disease progression. 4 The development and progression of POAG are influenced by complex gene/environment interactions, 5 as well as non-modifiable factors, including IOP, age, family history, central corneal thickness, and optic disc features. 6 …”
mentioning
confidence: 99%